The Authenticity Problem: Authenticity as a Methodological Trap in People-Centred Research on Working-Class Football Supporting Communities - Bland, Josh (Archaeologies, 2024)
This paper seeks to make a methodological contribution to archaeological praxis of working-class communities, by illuminating how archaeologists engaged in oral history-based research with working-class communities may encounter authenticity as a methodological challenge. Drawing on my PhD research on football as cultural heritage, I will outline the authenticity problem I encountered in the field: the enforcement of hierarchies of authenticity by working-class football supporters in response to their experiences of marginalisation in the sport. In turn, I will not only show how these hierarchies of authenticity present obstacles to researchers looking to build relationships of trust with their subjects, but also indicate some solutions to this authenticity problem. Specifically, I will show how it is often useful to “fall into the trap of authenticity” as a researcher and use the interview setting to discursively construct yourself as authentic on your subject communities’ own terms.